Smooth Solutions of a Class of Iterative Functional Differential Equations - Houyu Zhao (Abstract and Applied Analysis)
By Faà di Bruno’s formula, using the fixed-point theorems of Schauder and Banach, we study the existence and uniqueness of smooth solutions of an iterative functional differential equation x′(t)=1/(c0x[0](t)+c1x[1](t)+⋯+cmx[m](t)).